Pengaruh Kepemimpinan dan Fasilitas Sekolah Terhadap Kinerja Guru - Bahrudi Efendi Damanik; Dedi Suhendro (Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to determine the effect of leadership on teacher performance, to determine the effect of school facilities on teacher performance and to simultaneously determine the effect of leadership and school facilities on teacher performance. This research can be classified as associative research with a total sample of 41 people. The method used is a survey method. Data collection techniques are carried out by looking for supporting data from various literatures and journals, interviews, by collecting data by communicating directly with the object of research, observing data obtained from direct research results on activities carried out in the field, distributing questionnaires The questionnaire contains a list of questions related to the problem being studied for teachers. The conclusion of the study is that the leadership variable partially has a positive effect on teacher performance with a value of tcount > ttable 4,410 > 1,684, the school facilities variable partially has a positive effect on teacher performance with a value of tcount > ttable 5,734 > 1,684, the leadership variable and school facilities simultaneously have a positive effect on teacher performance with a value of Fcount > Ftable which is 16.517 > 3.320